Cooperation between Reverse Transcriptase and Integrase during Reverse Transcription and Formation of the Preintegrative Complex of Ty1 - Wilhelm, Marcelle (American Society for Microbiology, 2006)
Reverse transcriptase (RT) and integrase (IN) play a central role in the replication and transposition of retroelements. Increasing evidence suggests that the interaction between these two enzymes is functional and plays an important role in replication. In the yeast Saccharomyces cerevisiae retrotransposon Ty1, the interaction of IN with RT is critical for the formation of an active conformation of RT. We show here that the RT associated with VLPs is active only if it is in close interaction with IN. To probe the IN-RT cis-trans relationship, we have used a complementation assay based on coexpressing two transposons. We show that IN acts in cis to activate RT and that a functional integrase provided in trans is not able to complement replication and transposition defects of IN deletion or IN active-site mutant elements. Our data support a model in which IN not only interacts closely with RT during reverse transcription but also remains associated with RT during the formation of the preintegrative complex.